The Effect of Brainstorming Technique on the Students’ Reading Comprehension at SMA Swasta Gajah Mada Medan - Chandra Danil (elt, 2022)
This research deals with The impact of Brainstorming Technique towards the Reading Comprehension of SMA Swasta Gajah Mada Medan students. Brainscorming Technique was first developed by Alex. F. Osborn. Brainstorming Technique is a method of thinking up solution, finding ideas, and getting new concepts. In carrying out the research, Quantitative method was applied by the writer. Based on the findings from this research, applying Brainstorming Technique is more significant than aplying conventional teaching technique in teaching reading comprehension towards the students at grade X and Grade at SMA Swasta Gajah Mada Medan. According to the data, the mean scores of the students after taught by applying Brainstorming technique is 83.52. Standard deviation is 6,997after using Brainstorming Technique with 27 students. After using conventional teaching technique to 18 students in the control class, it was known that the mean scores are 71.11. Standard deviation is 5.102. Then it was known that the mean scores in the experimental class increased 19.63 points and the mean scores in the control class increased 12.22 points. From the calculation ot the t-test it can be seen that t-observed value was 5.38; t-test (5.38) is higher than t-table value (1,675) with p = 0.05 df = 43. This difference can indicate that Brainstorming Technique can significantly give effect on the students’ reading comprehension at SMA Swasta Gajah Mada Medan. Keywords: The Effect, Brainstorming Technique, Reading Comprehension